HIV clinic‐based extended‐release naltrexone versus treatment as usual for people with HIV and opioid use disorder: a non‐blinded, randomized non‐inferiority trial. (2nd March 2022) - Korthuis, P. Todd; Cook, Ryan R.; Lum, Paula J.; Waddell, Elizabeth Needham; Tookes, Hansel; Vergara‐Rodriguez, Pamela; Kunkel, Lynn E.; Lucas, Gregory M.; Rodriguez, Allan E.; Bielavitz, Sarann; Fanucchi, Laura C.; Hoffman, Kim A.; et al.
Abstract: Background and aim: Opioid agonist medications for treatment of opioid use disorder (OUD) can improve human immunodeficiency virus (HIV) outcomes and reduce opioid use. We tested whether outpatient antagonist treatment with naltrexone could achieve similar results. Design: Open‐label, non‐inferiority randomized trial. Setting: Six US HIV primary care clinics. Participants: A total of 114 participants with untreated HIV and OUD (62% male; 56% black, 12% Hispanic; positive for fentanyl (62%), other opioids (47%) and cocaine (60%) at baseline). Enrollment halted early due to slow recruitment. Intervention: HIV clinic‐based extended‐release naltrexone (XR‐NTX; n = 55) versus treatment as usual (TAU) with buprenorphine or methadone (TAU; n = 59). Measurements: Treatment group differences were compared for the primary outcome of viral suppression (HIV RNA ≤ 200 copies/ml) at 24 weeks and secondary outcomes included past 30‐day use of opioids at 24 weeks. Findings: Fewer XR‐NTX participants initiated medication compared with TAU participants (47 versus 73%). The primary outcome of viral suppression was comparable for XR‐NTX (52.7%) and TAU (49.2%) [risk ratio (RR) = 1.064; 95% confidence interval (CI) = 0.748, 1.514] at 24 weeks. Non‐inferiority could not be demonstrated, as the lower confidence limit of the RR did not exceed the pre‐specified margin of 0.75 in intention‐to‐treat (ITT) analysis. The main secondary outcome of past 30‐day opioid use was comparable for XR‐NTX versus TAU (11.7 versus 14.8 days; mean difference = −3.1; 95% CI = –8.7, 1.1) in ITT analysis. Among those initiating medication, XR‐NTX resulted in fewer days of opioid use compared with TAU in the past 30 days (6.0 versus 13.6, mean difference = −7.6; 95% CI = –13.8, −0.2). Conclusions: A randomized controlled trial found supportive, but not conclusive, evidence that human immunodeficiency virus clinic‐based extended‐release naltrexone is not inferior to treatment as usual for facilitating human immunodeficiency virus viral suppression. Participants who initiated extended‐release naltrexone used fewer opioids than those who received treatment as usual.